FT-IR spectroscopic study of preparation of lead zirconium titanate (PZT) by sol-gel processing - Oh, YJ; Hwang, IW; Shim, IB; Kim, YR (KOREAN CHEMICAL SOC, 1997)
Gelation time, gel structure and volatility of by-products during gelation of PZT sol-gel processing were investigated by FT-IR spectroscopy. FT-m spectroscopic study was performed on PZT gels with the various H2O contents (1, 2 and 3 mol) and the several types (HNO3, NH4OH) and amounts (0.1, 0.2 mol) of catalysts, monitoring temporal (0, 1, 3, 10 weeks, 3 months and 3 years) and thermal (100-700 degrees C) changes of FT-IR spectra. The interpretation of temporal change of the spectra revealed two trends. One is under the condition of 1 mol H2O, 1 mol H2O+0.1 mol HNO3, 3 mol H2O and the other is for 1 mol H2O+0.1 mol NH4OH, 2 mol H2O, 1 mol H2O+0.2 mol HNO3. The gel structures and the gelation times for these conditions were discussed in comparison with the reported results of SiO2, and we suggested the reaction mechanisms for these structural characteristics. Thermal variation of FT-IR spectra was interpreted as the evolution processes of gel by investigating the evaporation of solvent and the decomposition of organic residues.
Keywords: THIN-FILMS; ROUTE